Konstitusi dan Nomenklatur Kebebasan Beragama: Pengalaman Berbagai Negara - Ismatu Ropi (ILMU USHULUDDIN, 2020)
This article examines the idea of religious freedom as the constitutional rights of some countries. In the beginning, the principles of freedom of religion (liberty of religion) was deeply rooted and strongly associated with the concept of 'freedom of thought and conscience', a phrase that first appeared in the Westphalia Treaty of 1648 which ended a long war in the name of religion in Europe. In this context, religious freedom was understood as freedom to believe (or not believe), adhere (or not adhere) to a religious proposition, belief or doctrine on the basis of individual experience or reasoning. It also contained the freedom to change that belief at any time if desired for the reason that basically human being through out his/her life continues to carry out what to be called as the process of preference and selection from the 'better' life. Nevertheless, religious freedom is not merely a natural right belonging to every individual but in turn also a given right granted by the state as a political authority manifested later in the respective Constitution. For this reason, the state as the holder of the people's mandate has the right to take actions in maintaining this order which in turn may in principle be possible to limit the rights of the community itself, including those relating to religion. Hence this article discusses several important matters on the issue. First, how and to what extent international law guarantees religious freedom normatively; second, how do the general portrait of various state constitutions when discussing religious freedom, and third, to what extent freedom is practically influenced by conditions such as the concept of the public sphere and the existence of a dominant majority group.